Land Use Change in Ain Shkak Municipality (2004-2016) - وهبي, صالح; يوسف, بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
On a global scale, monitoring land-use and land-cover changes is important as it reflects spatial variations of human activities on the land surface and crucial for planning purposes. This study was conducted on the municipality of Ain Shkak, Japleh area , Lattakia city (18083.4 Dunums). The research aimed to monitor changes in land-use and land-cover between 2004 and 2016 using Geographic Information System (GIS). The results showed that the agricultural area decreased by 2.14% as there was increased residential use owing to population increase. The research findings offer new possibilities to conduct regional studies using GIS tools.